From Metal–Organic Frameworks to Single‐Atom Fe Implanted N‐doped Porous Carbons: Efficient Oxygen Reduction in Both Alkaline and Acidic Media - Jiao, Long; Wan, Gang; Zhang, Rui; Zhou, Hua; Yu, Shu‐Hong; Jiang, Hai‐Long (Angewandte Chemie (International ed.), 2018)
It remains highly desired but a great challenge to achieve atomically dispersed metals in high loadings for efficient catalysis. Now porphyrinic metal–organic frameworks (MOFs) have been synthesized based on a novel mixed‐ligand strategy to afford high‐content (1.76 wt %) single‐atom (SA) iron‐implanted N‐doped porous carbon (FeSA‐N‐C) via pyrolysis. Thanks to the single‐atom Fe sites, hierarchical pores, oriented mesochannels and high conductivity, the optimized FeSA‐N‐C exhibits excellent oxygen reduction activity and stability, surpassing almost all non‐noble‐metal catalysts and state‐of‐the‐art Pt/C, in both alkaline and more challenging acidic media. More far‐reaching, this MOF‐based mixed‐ligand strategy opens a novel avenue to the precise fabrication of efficient single‐atom catalysts. Iron islands: Based on a mixed‐ligand strategy, a porphyrinic MOF was pyrolyzed to afford high‐content single‐atom iron‐implanted N‐doped porous carbon (FeSA‐N‐C). Thanks to the FeSA sites, hierarchical pores, oriented mesochannels, and high conductivity, FeSA‐N‐C exhibits excellent oxygen reduction activity and stability, surpassing almost all non‐noble‐metal catalysts and Pt/C, in both alkaline and the more challenging acidic media.